Bobiku Brownie From Yellow Sweet Potato Flour As A High-Fiber Snack - Meilinasari, Meilinasari; P, Nanda Syura Pratiwi; Muntikah, Muntikah; Rabbani, Fairuz Dhia (Politeknik Kesehatan Kemenkes Jakarta II, 2024)
Diabetes mellitus (DM) is a non-communicable disease that is still a problem in Indonesia, with 19.5 million people aged 20 – 79 years in Indonesia suffer from it. Fiber is known to produce short-chain fatty acid which is beneficial for people with DM. Bobiku brownie with yellow sweet potato flour and stevia sweetener is an alternative snack for people with DM to meet the recommendations regarding fiber consumption. This study aims to determine the effect of the amount of yellow sweet potato flour used on the organoleptic quality and preference level of Bobiku brownies as a high-fiber snack. This research was experimental with completely randomized design by using 3 treatments and 3 replications. Organoleptic test was conducted by panelists. Energy and nutrient analysis were conducted a Saraswanti Indo Genetech Laboratory. The organoleptic test analysis results showed that different amount of yellow sweet potato flour used affected the aroma, texture, and preference level of Bobiku brownies (p<0.05). However, different amounts of yellow sweet potato flour used did not affect color and taste of Bobiku brownies. The product that panelists liked most was the brownie with 50 g of yellow sweet potato flour and 50 g of wheat flour. One serving (75 g) of brownies contained 228 kcal of energy, 7.6 g of protein, 6.14 g of fat, 34.7 g of carbohydrates, and 6.54 g of fiber. In the future, it is necessary to test the preference level on panelists who suffer from diabetes. Keywords: brownies, yellow sweet potato flour, fiber